Penerapan Metode TAM (Technology Acceptance Model) dalam Aktualisasi Sistem Informasi Rumah Sakit (SIMRS) - Sri Hartini Gea; Fransiskus Adhikara; Reza Hilmy (Jurnal Health Sains, 2022)
In recent years, information technology has become part of the power to run business activities. However, very few studies have examined the influence of the use of information technology SIMRS (Hospital Information System) in carrying out service operations in hospitals. The purpose of this research is to empirically examine the perceptions that influence the use of the SIMRS application for service operations at UKI Hospital Jakarta. The perceptions studied were: perceptions of benefits, perceptions of ease of use, and perceptions of user behavior. The model used to test technology acceptance is the Technology Acceptance Model (TAM). This study uses a quantitative approach using an ordinal scale in the form of a Likert scale 1-4. This type of research is an analytic study with a cross sectional design that was tested using SEM. The results show that perceived usefulness and perceived ease of use affect the actual use of the system. While the perception of user behavior has no significant effect